Sodium–Glucose Cotransporter 2 Inhibitors Work as a “Regulator” of Autophagic Activity in Overnutrition Diseases - Fukushima, Kazuhiko; Kitamura, Shinji; Tsuji, Kenji; Wada, Jun (Frontiers in Pharmacology, 2021)
Several large clinical trials have shown renal and cardiac protective effect of Sodium Glucose co Transporter 2 (SGLT2) inhibitors in diabetes patients, and the protective mechanisms need to be elucidated. There have been accumulating studies which report that SGLT2 inhibitors ameliorate autophagy deficiency of multiple organs. In overnutrition diseases, SGLT2 inhibitors affect the autophagy via various signaling pathways including mammalian target of rapamycin (mTOR), sirtuin 1 (SIRT1), and hypoxia inducible factors (HIFs) pathways. Recently, it turned out that not only stagnation but also overactivation of autophagy causes cellular damages, indicating that therapeutic interventions which simply enhance or stagnate autophagy activity might be "double-edged sword" in some situations. A small number of studies suggest that SGLT2 inhibitors not only activate but also suppress the autophagy flux depending on the situation, indicating that SGLT2 inhibitors can “regulate” autophagic activity and help to achieve the appropriate autophagy flux in each organ. Considering the complicated control and bilateral characteristics of autophagy, the potential of SGLT2 inhibitors as the regulator of autophagic activity would be beneficial in the treatment of autophagy deficiency.